Additional stress in soil embankments subjected to a new prestressed reinforcement device - Zhang, Qishu; Leng, Wuming; Xu, Fang; Yang, Qi; Ai, Xi (Journal of Civil Engineering and Management, 2019)
Theoretical solutions were derived to calculate the additional stress/prestress in a newly-developed prestressed embankment (PE), and the diffusion characteristics of the prestress in a PE with a lateral pressure plate (LPP) having width of 0.9 m were clarified using the theoretical solutions and a 3D finite element analysis. The results show that (1) the application of the theoretical solutions requires the net spacing between the LPP and the embankment shoulder is greater than the LPP width; (2) the maximum prestress appears in the upper part of the loading area of a LPP, and the maximum and minimum prestresses present an order of magnitude difference at the shallow depth, but the difference attenuates and the prestress gradually tends to be uniform with increasing depth; (3) the prestress propagates to the core zones that mainly bear the train loads with certain peak stress diffusion angles, and the values for the analyzed case are 50° and 58° in the external regions of the LPP along the slope and longitudinal directions, respectively; and (4) a continuous, effective and relatively uniform prestressing protective layer with a prestress coefficient greater than 0.1 can be formed above the core zones when the LPP spacing is properly designed.